From the History of the Textbooks Compiled to Teach Persian Language to Armenians (The Manuscript № 306 "Persian and Armenian Grammar) - Geghamyan, Astghik (Bulletin of Yerevan University B: Philology, 2023)
Among Iranian Armenians in the 16th-17th centuries, the revival of the Armenian school, which aimed to preserve the national, religious, and cultural identity of the Armenians in a Persian-speaking environment, also characterized national education and printing. Armenians living on the borders of the Iranian regime were forced to master spoken Persian due to the need for daily communication. Later, knowledge of written Persian also became relevant, as evidenced by a unique manuscript number 306 "Persian and Armenian Grammar" preserved in the scriptorium of Amenprakich Monastery of Saint New Julfa.  It was written in 1846. In Batavia, led by Patriarchate Father Nurses and Father Yovhannu Surenian and written by Georg Avetian Zakarianz Jughaetsi. In the preface, the information left by Gevorg Avetyan Zakaryants testifies that in the 19th century, there were completely new demands for the use of Persian among Iranian Armenians:  "My second country  New Julfa , there schools  established in  New Julfa by  a thoughtful and brave shepherd, children from our beloved nation will learn Persian apart from our Armenian." The manuscript consists of Persian grammar, versification, a Persian-Armenian dictionary, a translation, and the contents of Chapter 8 of Saadi’s “Golestan’’.  It is noteworthy that the manual begins with the teaching of the Persian alphabet and can be considered a holistic guide for teaching Persian.In the article, based on the manuscript textbook and lists of school subjects that have reached us, it is possible to determine the period when the Arabic script and the written Persian language became part of the educational work among the Armenians. Through the presentation and examination of the material found in the manuscript, the methodology of teaching written Persian among Iran-speaking Armenians is also introduced, comparing it with other Persian textbooks created for the locals in the same period. When studying the content of the manuscript, it is also important to understand how much "Golestan" contained in the textbook served as a teaching tool in the Armenian environment.
Keywords: grammar; manuscript; study guide; dictionary; school; written Persian; Arabic script; literary work; Golestan